ANALYSIS OF MARKETING STRATEGIES TO INCREASE USED MOTORCYCLE SALES AT MUHSHI MOTOR SHOWROOM IN BANDUNG CITY USING SWOT ANALYSIS - Dewanti, Vivayani Wahyu; Zaenal, Athian Fadly (Jurnal Manajemen Bisnis Dan Organisasi, 2025)
This study aims to examine the marketing mix and SWOT analysis in the marketing strategy of used motorcycle sales at the Muhshi Motor Showroom using a descriptive-qualitative approach. Based on the Marketing Mix method by Philip Kotler and Gary Armstrong, the marketing mix is defined as a set of controllable marketing variables that a company combines to elicit the desired response in the target market. The SWOT analysis systematically identifies various factors to formulate company strategies. This analysis is based on the logic of maximizing strengths and opportunities while minimizing weaknesses and threats. The results of the study using SWOT analysis of internal and external factors indicate that Muhshi Motor Showroom is positioned in Quadrant I (aggressive). This is a very favorable position, where the company has both opportunities and strengths, enabling it to maximize existing opportunities. Therefore, Muhshi Motor Showroom can implement strategies that support aggressive growth policies.